2020
DOI: 10.1186/s12883-020-01912-z
|View full text |Cite
|
Sign up to set email alerts
|

Severe cerebral edema induced by watershed shift after bypass in a patient with chronic steno-occlusive disease: a case report and short literature review

Abstract: Background: Carotid occlusive disease is a type of progressive disease resulting in ischemic stroke. Extracranialintracranial bypass surgery represents a valid therapeutic option when medical treatment does not make effects. The appearance of cerebral edema following bypass is common during acute stage. Additionally, there are many causes of mild cerebral edema, such as hemodynamic changes, venous congestion and others. However, severe edema involving large brain tissue, which presents as reversible aphasia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The progress of the acute ischaemic stroke would trigger local blood flow disorder, tissue ischaemia, hypoxia, and eventually, nerve cell necrosis. At this time, patients tend to present with various clinical symptoms such as hemiplegia and aphasia, indicating clinically gradual deterioration 26 . Penumbra was proposed for the first time on the basis of a research conducted by Abstrup 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progress of the acute ischaemic stroke would trigger local blood flow disorder, tissue ischaemia, hypoxia, and eventually, nerve cell necrosis. At this time, patients tend to present with various clinical symptoms such as hemiplegia and aphasia, indicating clinically gradual deterioration 26 . Penumbra was proposed for the first time on the basis of a research conducted by Abstrup 27 .…”
Section: Discussionmentioning
confidence: 99%
“…At this time, patients tend to present with various clinical symptoms such as hemiplegia and aphasia, indicating clinically gradual deterioration. 26 Penumbra was proposed for the first time on the basis of a research conducted by Abstrup. 27 In the early stage of ischaemia, cells in the ischaemic penumbra region will incur irreversible damage if blood flow cannot be recovered in time.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the continuous in-depth study of imaging technology and clinical understanding of carotid artery occlusion, an increasing number of clinical researchers have gradually realized that hemodynamic disorders play a crucial role in cerebral ischemia caused by carotid artery occlusion ( Tsukada et al, 2022 ). The study revealed that among patients with carotid artery occlusion receiving drug treatment ( Li et al, 2020 , 2022 ), the annual incidence of ipsilateral ischemic stroke was 3%, but the annual incidence of stroke increased to 10–20% in patients with severe cerebral hemodynamic disorders. The enhancement of brain hemodynamics has therefore received considerable attention from researchers.…”
Section: Introductionmentioning
confidence: 99%